2012
DOI: 10.1002/pola.26202
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of polybenzoxazine precursors using thiols: Simultaneous thiol–ene and ring‐opening reactions

Abstract: A new class of polybenzoxazine precursors of combined molecular structure of benzoxazine in the open and ring form has been developed. Thermally curable benzoxazine networks were obtained by simultaneous photoinduced thiol‐ene and Catalytic Opening of the Lateral Benzoxazine Rings by Thiols (COLBERT). The thiol‐ene reactions were initiated by photolysis of a free radical photoinitiator, 2, 2‐dimethoxy‐2‐phenyl acetophenone (DMPA), and the competing COLBERT reaction was triggered by thiol compound, 1,2‐ethanedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
39
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 57 publications
2
39
0
Order By: Relevance
“…In particular, COLBERT allows benzoxazine to polymerize even under ambient temperature. In our laboratory, we have utilized this reaction and demonstrated that cross-linked but additionally curable soft benzoxazine films can be prepared by simultaneous COLBERT and photoinduced thiol-ene reactions using difunctional thiol and diallyl functional benzoxazine [40]. Moreover, we have showed that benzoxazines can be used as a linker between two different polymers forming a block copolymer and COLBERT acted as a kind of thiol-oxazine click reaction to do so [41].…”
Section: Introductionmentioning
confidence: 94%
“…In particular, COLBERT allows benzoxazine to polymerize even under ambient temperature. In our laboratory, we have utilized this reaction and demonstrated that cross-linked but additionally curable soft benzoxazine films can be prepared by simultaneous COLBERT and photoinduced thiol-ene reactions using difunctional thiol and diallyl functional benzoxazine [40]. Moreover, we have showed that benzoxazines can be used as a linker between two different polymers forming a block copolymer and COLBERT acted as a kind of thiol-oxazine click reaction to do so [41].…”
Section: Introductionmentioning
confidence: 94%
“…Crosslinked but additionally curable soft benzoxazine films were prepared by simultaneous photoinduced thiol-ene and COLBERT reactions using difunctional thiol and diallybenzoxazine. [38] Similar approach was also used to form dual-cure hybrid polymer networks. [39] In a recent report from the authors' laboratory, it was demonstrated that benzoxazines can be used as a linker between two different polymers to form a block copolymer by using COLBERT as a ligation process in a manner of Thiol-X chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…[15] These materials offer low water absorption, high char yield, resistance against flame, high modulus, high strength, high glass transition temperatures, chemical resistance, long shelf life and very limited volumetric change upon curing. [15a, 16] The synthesis of these materials is performed by non-catalytic thermally activated ring opening of the corresponding benzoxazine monomers (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%